Respuesta :

(N-4)-3=3-(2n+3)
•distribute the negative symbol into the parentheses on the right side of the equation and combine like terms. This would leave you with n-7= -2n. Bring the variables to the left and numbers to the right.
3n= 7
•divide 3 from both sides of the equation
N= 7/3 or N= 2.3
Since the equation is (n-4)-3 = 3 - (2n+3):

By distributive property:
n-4-3 = 3 -2n -3

Variables on the right side, while constants on the left side: 
n+2n = 3
3n = 3

Divide both sides by 3:
n = 3/3
n = 1

Therefore, the value of n in the expression is 1.

I hope my answer has come to your help. Thank you for posting your question here in Brainly.

ACCESS MORE